Clinical situation of endemic Malaria in Yemen - Al-Mekhlafi, A.M.Q.; Mahdy, M.A.K.; Azazy, A.A.; Fong, M.Y. (2010)
Malaria remains a major public health problem causing mortality and morbidity in tropical and subtropical countries. A cross-sectional study was carried out to determine malaria prevalence and its clinical pattern during malaria season in Yemen. Blood samples were collected from 511 patients with fever who voluntary participated in this study, of them 268 were males and 242 females. Malaria was screened using Giemsa-stained thick and thin blood films. Clinical profile was recorded through physical and laboratory examinations and biodata were collected by pre-tested standard questionnaire. The overall prevalence was 15.3. Three malaria species (Plasmodium, falciparum, Plasmodium vivax and Plasmodium malarae) were detected with the predominance of P. falciparum (83.33). People living in the rural areas had higher infection rate compared to urban areas (p <0.005). Children were at higher risk of developing severe malaria compared to adults (p <0.05). Severe anaemia, respiratory distress, jaundice, convulsion and bleeding were more apparent among younger age groups of malaria cases compared to older children. The study indicates that malaria is still a public health problem with children being at high risk of developing severe malaria which may lead to death.